Attempted Suicide in the Older Adults: A Case Series From the Psychiatry Ward of the University Hospital Maggiore Della Carità, Novara, Italy - Gramaglia, Carla; Martelli, Maria; Scotti, Lorenza; Bestagini, Lucia; Gambaro, Eleonora; Romero, Marco; Zeppegno, Patrizia (Frontiers in Public Health, 2022)
Introduction: As suicide rates increase with age, it is mandatory to carefully assess old age suicidal behaviors. Our aim was to describe the main socio-demographic and clinical features of a sample of suicide attempters aged 65 years and older, and to assess differences within the sample (men vs. women; patients with vs. without a previous history of suicide attempt; patients with vs. without a previous psychiatric history). Methods: Retrospective study conducted at the Maggiore della Carità University Hospital, Novara, Italy. Results: A higher percentage of female patients in our sample were treated by or referred to mental health services, while a greater percentage of male patients required a prolonged clinical observation in the Emergency Room (ER) or in non-psychiatric wards before psychiatric admission. The percentage of patients without previous psychiatric history taking anxiolytic and sedative medications was 25%. Conclusion: It is likely that different clusters and types of suicide attempters exist. Women in our sample appeared more proactive in asking for help, and more likely to be already treated by or referred to a psychiatric service, suggesting the need to facilitate the access to psychiatric services for the male population aged 65 years and older, or to offer support and care for the non-psychiatric reasons (comorbidities, pain, and loss of autonomy) possibly underlying suicidal behavior in this specific group. The use of medications deserves more attention considering the possible critical diagnostic issues in this age group.